PERAN TOLL LIKE RECEPTORS (TLRs) PADA INNATE IMMUNITY (The Role of Toll Like Receptors to Innate immunity) - Hikmah, Nuzulul; Dewanti, I Dewa Ayu Ratna (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
TRLS is a homologous protein located at APC membrane cell worl as a functional receptor to activate leucocyte lead to onduce mentriger responsimun innate or inflamatory respons against palogenic againt. Functional receptor is associated wuth kinase respons to produce sitokyn and microbidal subtance. The aim of the study is to examine the respons to produce sitokyn and microbidal subtance. The aim of the study is to examine the role TLRs on innate immunity it is concluded that the role of TLRS is important functional receptor which activate leucocyte to induce mentriger respons imun innate or an inflamators respons against patogenic agent.